Avaliação do efeito da composição da solução dos poros na qualidade da passivação e resistência à corrosão da armadura do concreto - Modesti, Guilherme (Universidade do Vale do Rio dos Sinos, 2020)
Reinforced concrete structures have been deteriorating and showing performance decrease before than planned resulting in not only maintenance costs but also a bigger environmental impact due to the residues and materials consumption used in the repairs. Within the main pathological manifestations, the reinforcement corrosion stands out, usually related to the depassivation due to the carbonation, chlorides or sulfates. This study proposes the evaluation of the influence of the concrete pore solution characteristics (pH, ionic strength, chlorides contents and sulfates) in the electrochemical quality of passivation films, and the combined effect of pH and chlorides. For that, simulated concrete pore solutions were prepared with different chemical compositions, changing the pH and ionic strengths to verify the behavior of low carbon steel. Its influence on the passivation’s film quality was verified with electrochemical tests, such as open circuit potential, linear polarization resistance and electrochemical impedance spectroscopy. On a second opportunity, different chloride contents were added gradually, with electrochemical tests to verify its influence on the destabilization of the passivation film until corrosion. The results corroborate to the understanding that lower pH, such as 12, and lower ionic strengths lead to better passivation films than higher pH’s such as 13 when there isn’t chlorides. The lower electrical conductibility and, consequently, its higher charge transfer resistance, led to the formation of more stable passivation films. With chlorides, the behavior is the opposite, with the higher pH enduring a higher chloride concentration, prior of depassivation. Regarding the sulfates, it was aggressive to the passivation film due to the localized corrosion similar to chlorides. The results show that lower pH e IS solution, such as the ones originated from cements with supplementary cementitious materials lead to better passivation films without chlorides, however, they are less resistant when this ion is present.
Keywords: Corrosão; Força iônica; Soluções dos poros de concreto; Corrosion; Ionic strength; Concrete pore solutions; ACCNPQ::Engenharias::Engenharia Civil